Effectiveness of Guided Inquiry Based Student Worksheet Integrated with Flipped Classroom System on Reaction Rate Material on Students' Ability to Think Critically - Irma Khairunnisak; Mawardi Mawardi; Hayuni Retno Widarti; Sri Yamtinah (Postgraduate, University of Mataram, 2023)
This research aims to determine the effectiveness of guided inquiry based student worksheet integrated with flipped classroom system on reaction rate material on students' ability to think critically. This is a further development research with the type of quasi experiment and research design Non-equivalent control group design. In this study, two sample classes were used, namely control class and experiment class with a total sample size of 71 people who were taken using purposive sampling technique. After conducting the research, it is known that the n-gain value for the control class is 0.3 and the experimental class is 0.57, the difference in n-gain value is inferred that there is a difference in treatment in the two sample classes on student critical thinking skills. Furthermore, for hypothesis testing, the ttable value is 1.995 and tcount value is 6.13. Based on the results of data analysis, it is concluded that the use of guided inquiry-based student worksheet integrated with the flipped classroom system is effective in enhancing student critical thinking skills